Appearance comparisons, affect, body dissatisfaction and eating pathology in Portuguese female university students - Coelho, Carol (2023)
Physical appearance comparisons have been theorized to be associated with negative indicators of body image. This study aimed to study appearance comparisons and their association to affect, body dissatisfaction, and eating pathology. Three hundred and ten female university students with ages between 17 and 25 years (M = 20.2, SD = 1.9) completed sociodemographic and clinical data, self-reported questionnaires, and questions about appearance comparisons. Among the participants, 98.71% reported making appearance comparisons, and 42.15% of these reported making them frequently or always. Higher reported frequencies of appearance comparisons were related to higher levels of body dissatisfaction, negative affect, and eating pathology. Appearance comparisons to acquaintances were the most frequent. Comparisons in person and through media were reported in similar proportions. Upward comparisons were more frequent than lateral and downward comparisons and were related to higher levels of body dissatisfaction than downward comparisons and to higher levels of body dissatisfaction, negative affect, and eating pathology than lateral comparisons. Upward comparisons to close peers were associated with higher body dissatisfaction as opposed to models/celebrities. Results, limitations, and implications are discussed.